Editorial - Ratnalikar, N. V. (Journal of Engineering Education Transformations, 1998)
TTTI's occupy a significant position amongst the various types of Institutions-the IITs, Regional Engg. Colleges, State Engg. Colleges and poly technics imparting Engineering Education in the country. W7zen Established way back in sixties, their aim was "to train teachers of Diploma institutions, Promote research in design and development, classroom teaching and laboratory instruction, curriculum design &development, preparation of teaching aids, collaboration with industries etc." The search for quality in education had not commenced then, but institutions strived to acquire certain standard and fame. Later on, in eighties, TTTI's were assigned the additional tasks of assisting the Govts. in planning of Engineering Education, Â·in educational management, in shaping the educational policy and providing feed back as input to revision and modification of policy, from time to time.